2015
DOI: 10.11144/javerianacali.ppsi14-1.scsd
|View full text |Cite
|
Sign up to set email alerts
|

School Climate Associated with School Dropout Among Tenth Graders

Abstract: Objective. This study evaluated the association between high school dropout and six dimensions of school climate. Method. The sample consisted of 638 tenth graders who participated in the Healthy Teens Longitudinal Study. Participants attended school in Northeast Georgia, United States of America; they were surveyed even if they dropped out of school. Information about dropout was obtained through twelfth grade. Logistic regression was used to identify predictors of dropout. Results. More boys (22.1%) than gir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0
6

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 49 publications
1
9
0
6
Order By: Relevance
“…Okul terki riskini arttıran önemli faktörlerden biri ise okula aidiyet duygusunun düşük olması şeklinde belirtilmektedir (MEB, 2013;Osterman, 2000;Yorğun, 2014). Zorbaz (2018) ile Orpinas ve Raczynski (2016) tarafından yapılan çalışmalar okula aidiyet duygusu ile okul terki arasındaki ilişkiyi ortaya koymuştur. O'Connor (2018) tarafından yapılan çalışma da lise öğrencilerinin okula ait olma duygularındaki artışın, okul terk oranlarında yaşanacak düşüşün bir öngörücüsü olduğunu göstermiştir.…”
Section: çAlışmanın Gerekçesiunclassified
See 1 more Smart Citation
“…Okul terki riskini arttıran önemli faktörlerden biri ise okula aidiyet duygusunun düşük olması şeklinde belirtilmektedir (MEB, 2013;Osterman, 2000;Yorğun, 2014). Zorbaz (2018) ile Orpinas ve Raczynski (2016) tarafından yapılan çalışmalar okula aidiyet duygusu ile okul terki arasındaki ilişkiyi ortaya koymuştur. O'Connor (2018) tarafından yapılan çalışma da lise öğrencilerinin okula ait olma duygularındaki artışın, okul terk oranlarında yaşanacak düşüşün bir öngörücüsü olduğunu göstermiştir.…”
Section: çAlışmanın Gerekçesiunclassified
“…Araştırmanın, okula aidiyet duygusunu yordayan değişkenler ile ilgili sunduğu bulguların, okul terkini önleyici tedbirler alınması noktasında önem arz ettiği düşünülmektedir. Her ne kadar mevcut çalışmada okul terki ile okula aidiyet duygusu arasındaki ilişki araştırılmamış olsa da literatürde bu konuda yapılan birçok çalışma okula aidiyet duygusu ile okul terki arasında bir ilişki olduğunu ortaya koymuştur (O'Connor, 2018;Orpinas ve Raczynski, 2016;Zorbaz, 2018). Bu bağlamda okula aidiyet duygusunun düşük olması, okul terki riskini arttıran önemli bir faktör olarak belirtilmekte (MEB, 2013;Osterman, 2000) ve düşük aidiyet duygusunun, okul terki riskini beraberinde getirdiğini vurgulanmaktadır (Barber ve Schluterman, 2008;Kalaycı ve Özdemir, 2013).…”
Section: Tartışma Sonuç Ve öNerilerunclassified
“…The independent variables were: drug consumption, with "Yes" and "No" categories, emerged from the answers of teenagers to DUCI, which considers the substance consumption in the last 30 days prior to the interview; familial conviviality, related to the experience or non-experience with both parents; work and sexual and reproductive aspects (sexual relation, use of condom, pregnancy), also dichotomized in "Yes" and "No", and sociodemographic aspects, such as age, categorized up to 14/15 years old or more, according to criteria used in literature (9)(10)(11)(12) ; sex; religion, considering the assertion without distinction between religious diversities; race, grouped into "black", to those self-identified as Black and Two or More Races, and "white", to those self-identified as White and Asian, considering the categories defined by the Brazilian Institute of Geography and Statistics (IBGE).…”
Section: Study Protocolmentioning
confidence: 99%
“…Considering the complexity and magnitude of the phenomenon, scholars from various fields of knowledge dedicate themselves to the production of a knowledge that allows them to broaden the knowledge related to social and health aspects experienced by teenagers, exemplified by the use of alcohol and other drugs in adolescence (10)(11) . In this context, we question: What is the prevalence of intrafamilial violence experience?…”
Section: Introductionmentioning
confidence: 99%
“…Among Latina/o adolescents, school connectedness has been associated with positive behavioral and academic outcomes (Osterman, 2000;Sass, Castro-Villarreal, McWhirter, McWhirter, & Karcher, 2011), higher academic achievement and engagement (Croninger & Lee, 2001;Hargreaves, Earl, & Ryan, 1996), high school completion and postsecondary attendance (Niehaus, Irvin, & Rogelberg, 2016), and lower rates of delinquency and problem behaviors (Catalano, Haggerty, Oesterle, Fleming, & Hawkins, 2004;Sass et al, 2011;Thomas & Smith, 2004). In a recent study by Orpinas and Raczynski (2015), students who dropped out of high school reported significantly lower school connectedness and less meaningful participation in school compared to students who remained in school.…”
Section: School Connectednessmentioning
confidence: 99%